Halal detection technologies - Amid, Azura (Springer Singapore, 2024)
Halal detection technologies (HDTs) involve the latest tools to investigate products’ halal status, including food, cosmetics, pharmaceuticals, etc. The application of HDTs is acknowledged by the halal certification body (CB) worldwide since they become a confirmatory mechanism as part of the halal assurance system. However, analysts in halal-testing laboratories find difficulties in sample handling and choosing the suitable HDTs, the requirements to establish a validated and verified analytical method (AM), and (4) challenges against the HDTs. Hence, this chapter reviews these issues and recommends that analysts employ suitable HDTs in halal testing laboratories.